EFEKTIVITAS MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUKAN MEDIA PEMBELAJARAN WORDWALL TERHADAP HASIL BELAJAR MATEMATIKA - Izzah, Nurul; Cahyono, Anang Hadi; Kadarisman, Kadarisman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The purpose of this study is to assess how well third-grade children at SDN Lenteng Timur I learn mathematics when using the Game Based Learning (GBL) model, which is backed by the Jarimatika technique and Wordwall digital learning resources. Low multiplication performance among students is the main problem in the classroom, and it is ascribed to the persistence of traditional teaching methods and the lack of interactive technologies. This study employs a Nonequivalent Control Group approach model in a quasi-experimental approach. Pre-tests, posttests, observations, and documentation are the tools used to collect data. The GBL model is integrated with Wordwall to provide interactive and engaging learning experiences, while Jarimatika offers a concrete and enjoyable approach to mathematical operations. The findings reveal that the application of GBL in conjunction with Wordwall and Jarimatika significantly enhances students"Ÿ conceptual understanding and learning motivation. Students exhibited increased enthusiasm and active participation during the learning process, which positively influenced their academic achievement. These findings suggest that the integrated learning model is a creative and promising approach to raising primary school students' learning outcomes in mathematics.